The Influence of Post-Weld Tempering on the Mechanical and Microstructural Behaviour of AISI 1040 Carbon Steel Weld - Okuma, Silas; Oreko, Benjamin Ufuoma (Journal of Advanced Industrial Technology and Application, 2024)
his study examines the impact of post-weld tempering (PWT) on the mechanical behaviour of AISI 1040 carbon steel welds. To evaluate the effect of post-weld tempering on the mechanical properties of the welded joint, tensile and microhardness tests have been performed. Also scanning electron microscopy(SEM) was used to study the surface morphology of tempered steel weld samples.The findings revealed that the PWT samples exhibited greater ductility, whereas the sample tempered at PWT-5500C exhibited superior tensile strength (approximately 17% greater) than the other post-tempered and as-welded samples. The As-welded samples were found to have the highest hardness, this is as a result of the rich carbide precipitation at the grain boundaries caused by the welding process.The result further showed that the ductility and toughness properties of AISI 1040 carbon steel welds can be improved by post-weld tempering.The SEM study revealed that the degree of lath martensite formation increases with the tempering temperature. In addition, the studies further revealed that tempering AISI 1040 carbon steel welds at a temperature of 700°C produces the optimal equilibrium of mechanical properties for industrial applications.